Asymmetric synthesis of planar chiral carbonitriles and amines via carbene-catalyzed kinetic resolution - Lv, Ya (2024)
We have developed a catalytic method using chiral N-heterocyclic carbene (NHC) as the sole organic catalyst to synthesize planar chiral carbonitriles asymmetrically, resulting in optically pure, multifunctional compounds. The method demonstrates remarkable tolerance toward diverse substituents and substitution patterns through kinetic resolution (KR) or desymmetrization processes. The resulting optically pure planar chiral products hold significant potential for applications in asymmetric synthesis and antibacterial pesticide development.